(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
In this study, we observed the articulation and discursive construction on the theme of ecological-based agriculture in the cover stories of Globo Rural magazine. Our goal is to identify how Globo Rural constructs the discourse on ecological-based agriculture by acting in the tension between the discourses that circulate there. From the paths of meanings combined with the discursive framework, we reflect on the socio-cultural aspects in the magazine’s discourse. From them, we note the domination of economic rationality, which seeks to empty the discourse of environmentalism in the magazine politically and ideologically. Thus, we observe the operationalization of the “new rural economy” as a discursive framing of the Globo Rural, based on the market logic of hegemonic rurality and the appropriation of the ecological ideas of some counter-hegemonic ruralities.